Clinically tractable outcome prediction of non-WNT/non-SHH medulloblastoma based on TPD52 IHC in a multicohort study - Delaidelli, Alberto; Dunham, Christopher; Santi, Mariarita; Negri, Gian Luca; Triscott, Joanna; Zheludkova, Olga; Golanov, Andrey; Ryzhova, Marina; Okonechnikov, Konstantin; Schrimpf, Daniel; Stichel, Damian; Ellison, David W.; et al. (Clinical cancer research, 2022)
International consensus and the 2021 WHO classification recognize eight molecular subgroups among non-WNT/non-SHH (Group 3/4) medulloblastoma, representing approximately 60% of tumors. However, very few clinical centers worldwide possess the technical capabilities to determine DNA methylation profiles or other molecular parameters of high risk for group 3/4 tumors. As a result, biomarker-driven risk stratification and therapy assignment constitutes a major challenge in medulloblastoma research. Here, we identify an IHC marker as a clinically tractable method for improved medulloblastoma risk stratification.We bioinformatically analyzed published medulloblastoma transcriptomes and proteomes identifying as a potential biomarker TPD52, whose IHC prognostic value was validated across three group 3/4 medulloblastoma clinical cohorts (n = 387) treated with conventional therapies.TPD52 IHC positivity represented a significant independent predictor of early relapse and death for group 3/4 medulloblastoma [HRs between 3.67 and 26.7; 95% confidence interval (CI) between 1.00 and 706.23; P = 0.05, 0.017, and 0.0058]. Cross-validated survival models incorporating TPD52 IHC with clinical features outperformed existing state-of-the-art risk stratification schemes, and reclassified approximately 50% of patients into more appropriate risk categories. Finally, TPD52 immunopositivity was a predictive indicator of poor response to chemotherapy [HR, 12.66; 95% CI, 3.53-45.40; P < 0.0001], suggesting important implication for therapeutic choices.This study redefines the approach to risk stratification in group 3/4 medulloblastoma in global practice. Because integration of TPD52 IHC in classification algorithms significantly improved outcome prediction, this test could be rapidly adopted for risk stratification on a global scale, independently of advanced but technically challenging molecular profiling techniques.
Gesehen am 02.09.2022